Engaging for the Common Good: Typology, Motivation and Scope of Civic Engagement of Buddhists in Italy and Switzerland - Baumann, Martin (Journal of religion in Europe, 2025)
This article takes stock of and comparatively analyzes the scope and motivations of civic activities of Buddhists and Buddhist organizations in Italy and Switzerland. Based on the analytical perspective of civic engagement, we suggest discerning civic activities on a continuum from nonengagement to activist engagement, distinguishing the four types of nonengagement, intermediary, shaper, and activist. Further, the article differentiates four social motivations and four Buddhist motivations for civic engagement. The scope of civic engagement appears to be much larger in Italy than in Switzerland. The article formulates six hypothetical explanations for the difference, arguing that national and cultural specifics, differences in the legal system regarding the governance of religions, and the composition of the Buddhist populations are crucial in understanding the dissimilar scope of Buddhist civic engagement in the two countries.